Bill Nye the science guy/ Germs - Nye, Bill.; Disney Educational Productions (Elk Grove Village IL : Disney Educational Productions, 2003)
In GERMS, Bill uses foam models to illustrate the various types of germs and how they function. The recurring character, "Mamma Crust," motivates kids to brush their teeth, wash their hands, and cut way back on picking their noses.
Grade level: 4 and up.
DVD.
Keywords: Bacteria -- Study and teaching; Science -- Study and teaching; Children's films; Video recordings for the hearing impaired